PENGGUNAAN TEPUNG KULIT MANGGIS GARCINIA MANGOSTANA UNTUK MENINGKATKAN PERTUMBUHAN, INDEKS HEMATOKRIT DAN TINGKAT KELANGSUNGAN HIDUP IKAN MAS KOI CYPRINUS CARPIO - Dahlifa Dahlifa; Sutia Budi; Amal Aqmal (OCTOPUS : JURNAL ILMU PERIKANAN, 2016)
Increasing aquaculture production is one of the national program one Koi Fish Cyprinus carpio. Koi fish is a freshwater fish that has a high economic value due to have a wide variety of colour patterns beautiful body shape. Intensive farming methods developed at this time and the quality of the environment of diminishing give many implications to the emergence of stress levels in the cultivation of organisms, resulting in a low growth rate, which is not optimal pigmentation process and the quality of health of the fish declined. The skin of the mangosteen fruit contains tannins, saponins, flavonida, pectic substance, and iron. This study aimed to obtain information about the status of physiological stimulation immunostimulant Koi carp C. Carpio and evaluate dose Mangosteen peel flour in feed optimal to support growth Koi carp C. Carpio. Containers of research in the form of a jar size 15 L. Pets test form Koi fish. Test parameters such as the measurement of body weight, hematocrit index and survival rate. The results showed that the treatment of various concentrations of mangosteen peel flour in feed giving different values to growth, hematocrit index and survival rate Koi carp fish.